Racial Disparities in the Use of Catheter Ablation for Atrial Fibrillation and Flutter. Issue 12 (9th December 2014) - Tamariz, Leonardo; Rodriguez, Alexis; Palacio, Ana; Li, Hua; Myerburg, Robert
Abstract Background Atrial fibrillation (AF) is the most common arrhythmia seen in clinical practice. Catheter ablation is an expensive but potentially curable treatment of AF. We explored differences in the use of catheter ablation for AF in the state of Florida and compared the findings to ablation for atrial flutter. Methods We conducted a cross‐sectional analysis of all ambulatory and hospital discharge procedures between 2006 and 2009 in Florida. We identified all subjects with AF and atrial flutter, using International Classification of Diseases, 9th Revision codes along with the race/ethnicity of each individual. We used logistic regression to determine the odds ratio (OR) of having a catheter ablation per disease by race and ethnicity adjusted for Charlson score, insurance status, year of the procedure, and facility location. Results We identified 923 590 subjects with AF and 28 714 with atrial flutter. Catheter ablations were more commonly used in atrial flutter than in AF. The adjusted OR of having catheter ablation for AF for blacks was 0.67 (95% confidence interval [CI]: 0.60‐0.75, P < 0.01), and for Hispanics it was 0.83 (95% CI: 0.75‐0.91, P < 0.01) when compared to whites. The adjusted OR of having an ablation for atrial flutter for blacks was 1.08 (95% CI: 0.96‐1.21, P = 0.16), and for Hispanics it was 0.90 (95% CI: 0.78‐1.08, P = 0.20) when compared to whites. Conclusions In the state of Florida, black and Hispanic subjects with AF received less catheter ablations, whereas the same minority subjects with atrial flutter received a similar number of ablations compared to white subjects, with the same insurance and comorbidity burden.